Work Stress and Job Performance of Employees in System Operation Department at Tenaga Nasional Berhad - Siti Hassanah, Hassan (2011)
The study investigated the relationship between job stressor and job performance among staffs of System Operation department,Tenaga Nasional Berhad. The main objectives of the study is to determined; (i) relationship between workload and job performance; (ii) relationship between work ambiguity and job performance; (iii) relationship between family conflict and job performance. The data for this study were collected from staffs of System Operation Department at TNB only which consist of 105 employees include 30 female and 75 male, 85 executives and 20 non-executives but only 89 participate and gave the feedback. The majority of the employees are come from technical background include executives and non executives. The tests conducted were Multiple Regression and Pearson’s Correlation was carried out in answering the objectives of the research. The Pearson’s Correlation showed that only workload and family conflict have a relationship with job performance. However, multiple regression tests showed that overall job stressor give a significant impact to the job performance.